One country two systems. Competition regime in Mainland China and Hong Kong, which one is more conducive to western-foreign investors?’ - Arias Acuña, Gonzalo José (Revista Tribuna Internacional, 2019)
Hong Kong´s Competition Ordinance provides a framework of competition legislation that is more conducive to foreign investors than Mainland China. This is essential because HK´s regulatory framework of competition regulation has more common characteristics with western legislation, but also because of HK´s social, economic, legal and political history as a consequence of the United Kingdom influence. In that sense, western-foreign investors will look for a competition framework that provides clear, open and general rules.